Development of a Pain Management Protocol for a Paediatric Ward in the Gambia, West Africa - Lisa M. Puchalski Ritchie; Stephen R. C. Howie; Pamela Collier Njai (International Journal of Pediatrics)
Despite recent advances in our understanding of paediatric pain and its management, pain continues to be undertreated globally, particularly in children and in low income countries. This article describes the development of a paediatric analgesia and sedation protocol, tailored to the specific setting of the Medical Research Council (MRC) paediatric ward in the Gambia, West Africa. An iterative process was used throughout development, with inputs from the medical literature, local providers, and pain experts, incorporated to ensure a safe, effective, and locally appropriate protocol. We demonstrate that evidence-based published guidelines, can and should be adapted to allow for optimal pain management given the resources and capabilities of specific health care settings. It is hoped that the process and protocol described here, will not only help to improve care on the MRC ward, but serve as an example to others working toward improving pain management in similar health care settings.